Microinjection support system for small biological subjects. (April 2020) - Sugimoto, Yasuhiro; Naniwa, Keisuke; Aonuma, Hitoshi; Osuka, Koichi
Graphical abstract: Abstract: In biological research, various experiments such as behavioral experiments and physiological ones are often conducted with pharmacologically treated animals. In such experiments, it is necessary to inject the same volume of solution into numerous small animals, such as insects to prepare several experimental subjects. However, repeating manual injections is burdensome, and it is also difficult to maintain injection quality and consistency. We have developed a microinjection system that can support and semiautomate the injections of small animals. The system consists of two cameras, a micromanipulator, a syringe pump, and a structural framework all operated from a personal computer to quickly inject the same volume of liquid solutions at the same position and depth into small animals. The microinjection system has sufficient extensibility for it to be used in a variety of applications.